{μ-2-[(Benzothiazol-2-yl-2κN)hydrazonomethyl-2κN]-6-methoxyphenolato-1:2κ(3) O (1),O (6):O (1)}{2-[(benzothiazol-2-yl-1κN)hydrazonomethyl-1κN]-6-methoxyphenolato-1κO (1)}(methanol-2κO)(nitrato-2κO)dicopper(II) nitrate - Lin, Yu-Ching (International Union of Crystallography, 2009)
The title complex, [Cu(2)(C(15)H(12)N(3)O(2)S)(2)(NO(3))(CH(3)OH)]NO(3), has two Cu(II) centres coordinated by two deprotonated 2-[(benzothiazol-2-yl)hydrazonomethyl]-6-methoxyphenol ligands, a methanol molecule and a nitrate ion. Both Cu(II) centres are pentacoordinated in a distorted square-pyramidal fashion. The crystal structure is stabilized by N—H⋯O and O—H⋯O hydrogen bonds.